Literature Review Of Demographic Influences On Employee Performance In Manufacturing Companies In Developing Countries - Rachman, Tutut Arif; Soetjipto, Budi Eko; Wardana, Ludi Wishnu (PT Maju Malaqbi Makkarana, 2025)
This study aims to investigate and synthesize publications related to the demographic factors that affect the employee performance of manufacturing companies in developing countries. This study uses the SLR method with PRISMA steps. Articles filtered from the Sage Journals, Science Direct, Taylor & Francis journal databases, and additional ones from these databases with topics and keywords related to the influence of demographics on employee performance, with research locations in developing countries, published between 2023 and 2025, totaling 34,511 articles. After elimination according to the criteria, only 14 articles were considered and extracted. The results of the synthesis show that the demographic factors that influence are education level (hard skills and soft skills), age, and gender, in addition to the phenomena that influence demographics, such as culture in the work environment, and COVID-19, also affect employee performance. This research can be used by human resource managers in manufacturing companies as a consideration in managing employees, and this research can be used as a reference for further research.